Cost Management of Construction Projects. - Towey, Donald (Wiley, 2013)
The cost manager/quantity surveyor plays a pivotal role in the financial and contract management of construction projects, although the exact nature of the service they provide depends on the project employer's terms of engagement. This can mean acting as consultant in a range of roles including cost and advisory services for budget setting to initiate a project, cost management through the design and construction phases, contract administration and acting as the client side project manager to oversee the entire building process. Cost Management of Construction Projects focusse.